1999
DOI: 10.1099/13500872-145-2-357
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans ffh, a gene encoding a homologue of the 54 kDa subunit of the signal recognition particle, is involved in resistance to acid stress

Abstract: The ability of Streptococcus mutans, a bacterial pathogen associated with dental caries, t o tolerate rapid drops in plaque pH (acidurance), is considered an important virulence factor. To study this trait, Tn917 mutants of 5. mutans strain JH1005 which display acid sensitivity have been isolated and partially characterized. In this paper, the characterization of one of these mutants, AS1 7, is reported. Preliminary sequence analysis revealed that the transposon insertion in AS17 occurred in the intergenic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 47 publications
(54 reference statements)
3
64
0
Order By: Relevance
“…Both the inserts orf1 and ffh are known aciduric-related genes. The former encodes RNA-binding protein and a separate functional metagenomics study of the environmental sample confirmed its function [17], the latter comes from the S. mutans strain [11]. The purpose of construction of the strain E. coli DH10B/pSL-ffh and its functional verification was to detect whether the acid-resistant genes from oral bacteria could be heterologously expressed in E. coli .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the inserts orf1 and ffh are known aciduric-related genes. The former encodes RNA-binding protein and a separate functional metagenomics study of the environmental sample confirmed its function [17], the latter comes from the S. mutans strain [11]. The purpose of construction of the strain E. coli DH10B/pSL-ffh and its functional verification was to detect whether the acid-resistant genes from oral bacteria could be heterologously expressed in E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…After acid exposure, the intracellular pH decreases, and DNA is damaged. The cells can resist the acid stress through a variety of defence mechanisms, such as regulating the flow of protons inside and outside cells [11,13] and neutralizing intracellular protons through producing alkaline compounds [40]. Further, the DNA repair enzyme system can also assist cells to resist acid stress through repair of the damaged DNA [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rapid acidification is followed by expression of numerous proteins, including chaperones and membrane proteins, in a process necessary for cellular viability referred to as the acidtolerance response (12,13). Transposon mutagenesis in S. mutans resulted in several acid-sensitive mutants (14) and one mutation mapped to ffh within the sat (secretion and acid tolerance) operon (15). Surprisingly, interruption of ffh was not lethal (16), in contrast to what was reported for E. coli and B. subtilis (3,17), but did render S. mutans sensitive to acidic pH.…”
mentioning
confidence: 99%